(untitled) (Andamios, Revista de Investigación Social, 2009)
Democratization has led to fairer Mexican elections and increasingly shared power among political parties, which have created legislatures that are more active and independent of the executive. However, it has not been entirely clear to what extent this process of political change has produced an increased capacity of legislatures to exercise its role as a counterweight to the executive branch. In this sense, this paper examines various issues of the electoral system and party system—esspecially the ban on consecutive legislative re-election—that have shaped a weak institutional framework of legislative bodies. In this perspective, it is argued that it should go beyond the approaches that set up the increase of the party competition and the legislative pluralism have strengthened the oversight function of the Congresses.